Towards an effective model for (d,p) and (d,n) nucleon-transfer reactions to bound states for FLUKA - Salvat-Pujol Francesc; Ferrari Alfredo (EPJ Web of Conferences, 2020)
A general overview is presented of an effective model for the inclusion of (d,p) and (d,n) nucleon transfer direct reactions to bound states of the residual nucleus in the general-purpose radiation-transport code FLUKA. The model relies on the distorted-wave Born approximation, employing state-of-the-art subroutines for the numerical solution of the radial Schrödinger equation for the deuteron- and nucleon-nucleus wave-functions, as well as contemporary optical potential models for the latter two. A final variation of a handful of deuteron optical potential parameters provides the model with additional flexibility and enhances the agreement with experimental nucleon angular distributions in a considerable range of target nuclei and deuteron energies.